Barriers to Research Faced by High‐Income Versus Low‐ and Middle‐Income Country Otolaryngologists and Otolaryngology Residents - Nader G. Zalaquett; Mohamad Al Mir; Rita Maria Jalkh; Sarah Nuss; Akansha Pandey; Rolvix H. Patterson; Jad Hosri; Randa Al Barazi (OTO Open)
Abstract Objective This study aims to compare research productivity and barriers to research between high‐income countries (HICs) and low‐ and middle‐income countries (LMICs) otolaryngologists. Study Design Cross‐sectional survey. Setting International survey. Methods A survey developed by members of the Lebanese Otolaryngology Research and Awareness Group was disseminated globally to otolaryngologists and otolaryngology residents. The survey assessed research efficiency, funding, and perceived barriers. Data were analyzed using t tests and χ2 tests. Results A total of 82 responses from 21 countries were recorded, with 33 from HICs (40.2%) and 49 from LMICs (59.8%). LMIC respondents reported significantly less research funding (84.4% vs 60.6%, P = .013) and fewer publications (24.4% vs 3.1%, P = .001) compared to HIC respondents. LMICs faced unique individual barriers like elderly care responsibilities (17.8% vs 0%, P = .035). Organizational challenges in LMICs included limited access to information sources (35.7% vs 15.6%, P = .017) and financial resources (85.7% vs 40.6%, P < .001). Institutional challenges such as lack of funding (83.3% vs 34.4%, P < .001) and protected research time (71.4% vs 56.3%, P = .047) were more prominent in LMICs. Governmental barriers were also greater in LMICs, including demotivating government policies (59.0% vs 9.4%, P < .001). Additionally, covering article processing charges was a significant challenge for 76.2% of LMIC respondents compared to 31.3% in HICs (P = .001). Conclusion Otolaryngologists in LMICs encounter substantial barriers to research productivity compared to those in HICs, primarily due to funding gaps, lack of institutional support, and unfavorable governmental policies. Addressing these disparities is essential for fostering equitable global research contributions.